APOTHEOSIS: An Efficient Approximate Similarity Search System for Digital Forensics - Huici, Daniel; J. Rodríguez, Ricardo; Mena, Eduardo (Jornada de Jóvenes Investigadores del I3A, 2024)
APOTHEOSIS is a similarity search system that enables fast identification of similar digital artifacts within large volumes of data. It uses approximate search techniques and approximate similarity matching algorithms for efficient detection. It was evaluated with a Microsoft Windows processes dataset, validating its functionality.